GeoTrack: Enhancing RSBSA through GIS in Mat-I, Claveria, Misamis Oriental - Joshua Mervin V. Batiancila; Junna Mitchelle C. Mapalo; Evon Q. Maxilom; Jay-Ar P. Nagandang; Janelle Bernal Toquero; Aubrey A. Lavarez (Universitas Multi Data Palembang, 2026)
GeoTrack enhances the Registry System for Basic Sectors in Agriculture (RSBSA) in Mat-i, Claveria, Misamis Oriental by addressing limitations of spreadsheet-based data management that restrict visualization and analysis. The system integrates Geographic Information System (GIS) technology to provide spatial mapping, farmer profiling, and agricultural data management through a web-based platform. Developed using open-source tools and an iterative software development life cycle, GeoTrack supports efficient data storage, real-time updates, and interactive map publishing. System usability was evaluated using the System Usability Scale (SUS), yielding an effective score of 88.5%, indicating excellent user satisfaction and performance. Results show improved accessibility, visualization, and decision-making for local agricultural stakeholders. The system enables better planning through color-coded maps, automated reports, and centralized records. Continuous training and infrastructure improvements are recommended to ensure scalability and long-term adoption across additional barangays.